Re-editing of Hegemonic Power Relations in American Corporate Geopolitics - Cetin, Beyzade Nadir (Istanbul Univ, Fac Letters, Dept Sociology, 2016)
The prospective system of stratification betaes is countries, quintessentially,should be analyzed in the frame of their effects on the global system. To analyze a global system of stratification means to analyze the hegemonic power relations. When analyzing, we consider countries, which affect systems within their own power and have leverage on other countries, as hegemony, and we consider domination or power, which is constructed by them, as hegemony This study attempts to show that hegemonic power relations constructed by the system are revealed by following the historical traces of their changing and transforming structures. These differences, which are the results of the changing and transforming hegemonic power relations, were examined. The traces of these changes and transformations were analyzed with American corporate geopolitics, which conceptualizes the geopolitical partnership between the American government and global corporates to maintain the American world leadership.
Keywords: Hegemony; Hegemonic power structuring; Global capitalist classes; World leadershi; American corporate geopolitics